Impact factors on Portuguese hotels' liquidity - Luís Lima Santos; Conceiç\~ao Gomes; Cátia Malheiros; Ana Lucas (Journal of Risk and Financial Management, 2021)
As a core activity in the tourism sector, hospitality accounts for the largest share of the sector's revenue. The last few years, prior to the COVID-19 pandemic, have been years of strong growth both in the number of hotel companies and in the number of available rooms. The hospitality industry has also been betting on diversification as well as on the quality of its services. This activity has a strong impact on the various agents in the sector, thus it makes it essential to measure and analyze the sustainability of these hotels. One of the indicators that proficiently measure short-term sustainability is the company's liquidity level, as it demonstrates its ability to meet short-term financial obligations. This type of indicator is useful since it provides relevant information not only for managers, but also for banks and lenders, and investors. Volatility is a characteristic of hotels which are associated with geographic location, implying changes in the main operating revenue indicators. In this sense, this research aimed to investigate if the ability to reimburse short-term responsibilities differs according to the geographic location, food and beverage service existence, official stars classification, and hotel size. Portuguese hotels with and without restaurants were analyzed in the 2013-2017 period and the number of available rooms and star rating were included in the database. All the information was obtained on SABI (a database of detailed financial information of Portuguese and Spanish companies) and RNET (the Portuguese Register of Tourist Enterprises). Findings show that the behavior of some hotels concerning short-term obligations does not differ much considering the location of the hotels. However, the Algarve and the North region have the highest values. In fact, the official star rating proved to have the greatest influence. The size of the hotels, as well as the existence of restaurants negatively influences liquidity. This information is very important for hotel investors. This study can also provide management information that allows more informed decision-making as well as the definition of corrective measures if necessary.
Keywords: 330; financial ratios; geographic location; hospitality management; hotel dimension; liquidity; Portuguese hotels; restaurants; stars rating